Intraocular pressure change after phacoemulsification in angle‐closure eyes without medical therapy. Issue 6 (June 2017) - Atalay, Eray; Nongpiur, Monisha E.; Baskaran, Mani; Perera, Shamira A.; Wong, Tina T.; Quek, Desmond; Aung, Tin
Abstract : Purpose : To evaluate the intraocular pressure (IOP) change and associated factors 6 months after phacoemulsification in eyes with primary angle‐closure suspect (PACS) and eyes with primary angle closure (PAC) that had no medical therapy. Setting : Singapore National Eye Center, Singapore, Singapore. Design : Retrospective case series. Methods : Patients with PACS or PAC (with corrected distance visual acuity <20/40) who had uneventful phacoemulsification were recruited. Patients were excluded if they were on IOP‐lowering medications within 6 months preoperatively and postoperatively. Preoperative gonioscopy, A‐scan biometry, anterior segment optical coherence tomography, and automated refraction were reviewed. Factors related to the percentage of and absolute IOP change were assessed using multiple linear regression analyses after adjusting for age, sex, and diagnosis. Results : The study evaluated 85 patients (85 eyes; 52 PACS, 33 PAC) after 7 eyes (1 PACS, 6 PAC) were excluded because of poor quality imaging. Overall, IOP decreased by 19.9% from the preoperative mean of 16.1 mm Hg ± 3.1 (SD) to 12.9 ± 2.7 mm Hg. The IOP change between the PACS group (−3.3 ± 2.8 mm Hg; −20.6%) and the PAC group (−3.2 ± 4.7 mm Hg; −19.6%) was similar ( P > .05). In multiple linear regression analyses, a higher preoperative IOP (β = 0.68, P < .001) and fewer clock hours of peripheral anterior synechiae (PAS) (β = −0.30, P = .03) predicted a greater absolute change in and percentage of reduction in IOP, respectively. Conclusions : The mean IOP reduction 6 months after phacoemulsification was 20%. Less IOP reduction was observed in the presence of lower preoperative IOP and more extensive PAS.